Perbedaan Pengaruh Latihan Core Muscle (Variasi Plank dan Variasi Squat) terhadap Peningatan Hasil Lemparan Ke dalam Pemain Akademi Arema FC U-16 - Riko Wahyu Prasetiyo; Mahmud Yunus; Heri Purnaman Pribadi (Lembaga Pengembangan Kinerja Dosen, 2024)
Football requires players to master the basic techniques of playing football, one of which is the Throw-In. Football players can improve throw-ins through Core Muscle Training with plank variations and squat variations. The Arema FC U16 Academy has a specific training program to improve Throw-In abilities. This research method uses a quasi-experimental method with a